Crosstalk Between MicroRNAs and Circular RNAs in Human Diseases: A Bibliographic Study - Chen, Yu-Meng; Zheng, Yi-Li; Su, Xuan; Wang, Xue-Qiang (Frontiers in Cell and Developmental Biology, 2021)
Background: Crosstalk of circRNAs and miRNAs refers to the communication and co-regulation between them. Circular RNAs (circRNAs) can act as microRNAs (miRNAs) sponges, and miRNAs can mediate circRNAs. They interact to regulate gene expression and participate in the occurrence and development of various human diseases. Methods: Publications on the crosstalk between miRNAs and circRNAs in human diseases were collected from Web of Science. The collected material was limited to English articles and reviews. CiteSpace and Microsoft Excel were used for bibliographic analysis. Results: A total of 1013 papers satisfied the inclusion criteria. The publication outputs and types of researched diseases were analyzed, and bibliographic analysis was used to characterize the most active journals, countries, institutions, keywords, and references. The annual number of publications remarkably increased from 2011 to 2020. Neoplasm was the main research hotspot (n = 750 publications), and Biochemical and Biophysical Research Communications published the largest number of papers (n = 64) on this topic. Nanjing Medical University ranked first among institutions actively engaged in this field by publishing 72 papers, and China contributed 96.84% of the 1013 papers (n = 981 publications) analyzed. Burst keywords in recent years included glioblastoma, miR-7, skeletal muscle, and non-coding RNA. Conclusions: Crosstalk between miRNAs and circRNAs in human diseases is a popular research topic. This study provides important clues on research trends and frontiers.